2016
DOI: 10.4103/0976-3147.196461
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Calcium Levels with Infarct Size in Acute Ischemic Stroke: Observations from Northeast India

Abstract: Background:Calcium is known to be major mediator in ischemic neuronal cell death. Recent studies have shown that elevated serum calcium levels at admission in patients with stroke have been associated with less severe clinical deficits and with better outcomes.Aim:The aim of this to determine the correlation between serum calcium (total, corrected, and ionized) and infarct size (IS) in patients with acute ischemic stroke.Materials and Methods:Data were collected from 61 patients presenting with acute ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Ca 2+ ions play a vital role as a major initiator and activator in the ischemic cell death pathways [ 15 ]. Elevated levels of intracellular Ca 2+ ions in serum plays a role in decrease of infarct volume and outcome in ischemic stroke patients [ 11 , 12 , 48 ]. Ca 2+ accumulation triggers mitochondrial damage and contributes to delayed neuronal death as well as ROS [ 15 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ ions play a vital role as a major initiator and activator in the ischemic cell death pathways [ 15 ]. Elevated levels of intracellular Ca 2+ ions in serum plays a role in decrease of infarct volume and outcome in ischemic stroke patients [ 11 , 12 , 48 ]. Ca 2+ accumulation triggers mitochondrial damage and contributes to delayed neuronal death as well as ROS [ 15 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another Indian study by Borah M, et al . [ 13 ] found that a negative correlation was found between serum calcium levels and infarct size in acute ischemic stroke. In contrast, one study by Chung JW, et al .…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our study, one study reported that total serum Ca 2+ levels in the early stages of AIS (< 4.5 h) was not associated with long‐term outcome (Ovbiagele et al., 2008 ). However, some studies reported their relationship: (1) low level of serum calcium was obviously associated with poor outcome (Chung et al., 2015 ; D'Erasmo et al., 1998 ) and more severe neurological deficit (Guven et al., 2011 ; Ishfaq et al., 2017 ; Ovbiagele et al., 2006 ), and bigger infarction volume (Borah et al., 2016 ; Buck et al., 2007 ) of ischemic stroke patients; (2) high levels of albumin‐corrected calcium, but not serum calcium are associated with a poor discharge outcome and a higher incidence of mortality after AIS (Chung et al., 2015 ); (3) an increased risk of poor functional outcome was found in the third quartile group and an increased risk of all‐cause mortality in the top quartile group of serum albumin corrected calcium levels within 24 h of hospital admission in patients with AIS and transient ischemic attack (Zhang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%